Corporate Social Responsibility for takaful industry’s branding image - Muhamad Fazil Ahmad,; Siti Zakiah Melatu Samsi,; Rosmawati Mohamad Rasit,; Norzita Yunus,; Norhayati Rafida Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study attempts to confirm the likelihood of Corporate Social Responsibility (CSR) activities giving different effects on brand image components and whether corporate reputation mediates these effects. Four action-based types of CSR, namely the economic, legal, ethical and philanthropic, were analyzed and tested in this study. This study employs quantitative method of analysis whereby the participants were exposed to different treatments and the brand image was divided into an affective, specific and generic cognitive elements. A total of 327 (N = 2110) stakeholders of Takaful; the agents/ operators in Kuala Terengganu, Malaysia were involved. Using the Structural Equation Model analysis, the affective component of the brand image showed a greater impact on the commitment towards the four types of CSR as compared to the others. The results revealed that the economic and philanthropic CSR activities significantly led to a more positive level of both brand image components and corporate reputation management than legal and ethical CSR activities. In addition, brand image has positively influenced the betterment of corporate reputation management. These findings have significant implications for future research directions in the corporate communication perspective.